(untitled) (Scientific journal of the Fergana State University, 2023)
Turkestan soap root (local name Beh, Etmak), or Allochrusa gypsophiloides is the best known endemic saponin-bearing plant of Central Asia. Ultrahigh performance liquid chromatography-electrospray ionization-mass spectrometry (UPLC-ESI-MS) was applied to the analysis of the compounds of the roots of A. gypsophiloides. Through UPLC-ESI-MS studies on the plant methanol extract 2 major triterpene saponins were detected and identified as bisdesmosides of gypsogenin (A) and quillaic acid (B).